2015
DOI: 10.1002/cbf.3123
|View full text |Cite
|
Sign up to set email alerts
|

Changes in glucose transporter expression and nitric oxide production are associated with liver injury in diabetes

Abstract: In diabetes mellitus (DM), both hyperglycaemia and hyperlipidaemia can initiate accumulation of fat in the liver, which might be further mediated by inducible nitric oxide synthase. We have studied changes in GLUT1, nitric oxide (NO(·)) concentration and liver damage in two rat DM models. STZ model was induced by strepozotocin 50 mg/kg. HS model was induced by high-fat diet and 30 mg/kg streptozotocin. GLUT1 expression was studied by means of real-time RT-PCR and immunohistochemistry. Production of NO(·) was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…C‐reactive protein was a parameter increased in patients with liver steatosis and correlated with intrahepatic fat content in our study. Increased CRP values indicate on inflammation that is one of the factors associated with liver steatosis and metabolic syndrome . Therefore, CRP might be considered for development of novel biomarkers for liver steatosis assessment in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…C‐reactive protein was a parameter increased in patients with liver steatosis and correlated with intrahepatic fat content in our study. Increased CRP values indicate on inflammation that is one of the factors associated with liver steatosis and metabolic syndrome . Therefore, CRP might be considered for development of novel biomarkers for liver steatosis assessment in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A tight relationship exists between various chronic metabolic diseases, such as obesity, type 2 diabetes, and non-alcoholic fatty liver disease (NAFLD), all of them reaching epidemic dimensions on a global scale [258]. While NAFLD increases type 2 diabetes incidence and the occurrence of late complications, type Table 1 Overview of main GLUTs in the liver, muscle, and adipose tissue and their tissue-specific function in metabolism Tissue Isoform Tissue-specific function in metabolism Liver GLUT1 Postnatal development and organogenesis of the liver [89]; main glucose transporter in non-parenchymal cells, relatively low levels in hepatocytes [221]; elevated in non-alcoholic steatohepatitis (NASH), alcoholic liver disease (ALD) [109], and hepatocellular carcinoma (HCC) [267]; reduced surface expression in hepatitis C virus (HCV) infection [111]; may contribute to glucotoxicity and oxidative stress [220] GLUT2 Most abundant GLUT isoform in hepatocytes, responsible for bulk of glucose uptake, but does not directly mediate hepatic glucose output [80]; involved as hepatoportal glucose sensor [20,21]; SLC2A2 deficiency causal for Fanconi-Bickel syndrome (FBS) [61,144]; gene variants have been associated with fasting hyperglycemia, transition to type 2 diabetes, hypercholesterolemia, and the risk of cardiovascular diseases [60]; downregulated in HCV infection [111] GLUT5 Fructose transport, dietary fructose consumption associated with increased expression, non-alcoholic fatty liver disease (NAFLD)…”
Section: Liver Insulin Resistance Is a Major Feature Of Type 2 Diabetmentioning
confidence: 99%
“…Interestingly, GLUT1 expression is also increased in hepatocytes in both fasting and diabetic states. It is unclear, however, whether these alterations are triggered rather by low circulating insulin levels or by hyperglycemia [220,231]. In the context of microvascular complications, however, decreased GLUT1 levels in the retina have been described to be beneficial in the prevention of retinopathy as a diabetic late complication [134].…”
Section: Glut1: Marker For Oncogenic and Metabolic Diseases In The Livermentioning
confidence: 99%
“…In fact, other studies have reported an increased NO concentration in serum and tissues (Yang et al, 2014;Sokolovska et al, 2015;Varsha et al, 2015) and inducible nitric oxide synthase (iNOS) overexpression in STZ-induced diabetic rats (AlRejaie et al, 2015). In this context, we observed an increase in NO levels not only in pancreas, but also in the liver and kidneys of DM and/or C. albicans-infected animals, which can be related to the fact that besides of the enhancement in interactions of superoxide with NO in the oxidative diabetic environment, NO is involved in pathogen killing mechanism and contributes to damage in other tissues (Shahani and Sawa, 2011;Samarghandian et al, 2013).…”
Section: Discussionmentioning
confidence: 98%